Family structure and use of prenatal care - Elisabete Alves; Susana Silva; Simone Martins; Henrique Barros (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
This cross-sectional study intended to assess the use of prenatal care according to the family structure in a population with free universal access to prenatal care. In 2005-2006, the Portuguese birth cohort was assembled by the recruitment of puerperae at public maternity wards in Porto, Portugal. In the current analysis, 7,211 were included. Data on socio-demographic characteristics, obstetric history, and prenatal care were self-reported. Single mothers were considered as those whose household composition did not include a partner at delivery. Approximately 6% of the puerperae were single mothers. These women were more likely to have an unplanned pregnancy (OR = 6.30; 95%CI: 4.94-8.04), an inadequate prenatal care (OR = 2.30; 95%CI: 1.32-4.02), and to miss the ultrasound and the intake of folic acid supplements during the first trimester of pregnancy (OR = 1.71; 95%CI: 1.30-2.27; and OR = 1.67; 95%CI: 1.32-2.13, respectively). The adequacy and use of prenatal care was less frequent in single mothers. Educational interventions should reinforce the use and early initiation of prenatal care.